An LC–MS/MS method for determination of bioactive components of liquorice and Semen Strychni in rat plasma: Application to a pharmacokinetics study. Issue 2 (26th July 2017) - Zhang, Min; Deng, Yang; Wang, Chao; Cai, Hua‐Lin; Wen, Jing; Fang, Ping‐Fei; Zhang, Bi‐Kui; Li, Huan‐De; Yan, Miao
Abstract : Semen Strychni is known for its treatment of rheumatic arthritis with a low therapeutic index. Liquorice contributes a lot in herb detoxification according to the traditional Chinese medicine theory. A simple, rapid, and sensitive liquid chromatography–mass spectrometric method (LC–MS) was developed and validated for simultaneous determination of main bioactive ingredients in liquorice and Semen Strychni in rat plasma. Using moclobemide and cyproterone acetate as the internal standards, the analytes were pretreated via protein precipitation with methanol. An Ultimate AQ‐C18 column (3.0 μm, 3.0 × 100 mm) was employed for chromatographic separation, combining with gradient elution. The mobile phase consisted of 0.07% formic acid and 0.12% ammonium acetate in aqueous phase (A) and acetonitrile in organic phase (B). The elution program was as follows: 0–0.5 min, 20% B; 0.5–1 min, 20–60% B; 1–7 min, 60–85% B; and 7–7.5 min, returned to 20% B, then continued to 12 min. Selected reaction monitoring was performed in both positive and negative ESI. Positive mode was adopted for detection of strychnine, brucine, and moclobemide, while negative mode was used for glycyrrhizic acid, glycyrrhetinic acid, liquiritigenin, isoliquiritigenin, liquiritin, and cyproterone acetate. The method was validated for specificity, linearity, matrix effect, recovery, precision, accuracy, and stability. The results show that this method is sensitive, accurate and robust for biological matrix analysis. Moreover, the proposed method was applied to a pharmacokinetic study in Sprague–Dawley rats for investigating the mechanism of which liquorice detoxifies Semen Strychni. Abstract : A HPLC‐MS/MS method for the determination of three different types of compounds in rat plasma was developed and fully validated. The quantitative method was then successfully applied to a pharmacokinetic study after oral administration of brucine and subsequent (30 minutes later) licorice extracts for detoxification in Sprague‐Dawley rats. The findings would be beneficial for evaluating the ADME and underlying detoxification mechanism of licorice, as well as the safety clinical application of Semen Strychni.